New oilseed - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
An inconspicuous wild plant discovered by chance in Ethiopia could become an important industrial oil crop of benefit to many ACP countries. The plant is Vernonia galamensis, a common annual herbaceous weed that thrives in many dry parts of Africa...